NASA's Capability Evolution Toward Commercial Space. (November 2019) - Heracleous, Loizos; Terrier, Douglas; Gonzalez, Steven
Abstract: We discuss how the space industry moved from a government dominated field to a commercially driven field. In the context of this industry shift, we explore how NASA's capabilities developed from its early hierarchical model to the intergovernmental and then commercial network models. We refer in particular to NASA's organizational, cultural, relational, and technological capabilities. These developments over time suggest that these are dynamic capabilities that respond to the demands of the external environment and to mission imperatives.